Effects of Culture Conditions on Growth and Production of Xylonic Acid using Recombinant E. coli BL21 (DE3) - Rafidah, Mohamed Ali Hanapiah; Rozaimi, Abu Samah; Nurul Atikah, Mohd Rodzri; Mior Ahmad Khushairi, Mohd Zahari; Wan Salwanis, Wan Md. Zain (Elsevier Ltd, 2019)
Xylonic acid is one of the top 30 highly valuable chemicals that can be obtained by microbial conversion. One of the recently used microorganisms to produce xylonic acid from xylose is the recombinant Escherichia coli. In this study, the effect of medium and nitrogen source concentration on the growth of the recombinant E. coli BL21 (DE3) and xylonic acid production were investigated. The fermentation was carried out in shake flasks for 24 h at 37 °C and 200 rpm. Hydroxamate analysis was performed to determine the concentration of xylonic acid. The recombinant E. coli BL21 (DE3) produced up to 8.69 g/L xylonic acid with yield of 0.86 g/g from 10 g/L xylose in SOB medium with 20 g/L tryptone and 5 g/L yeast extract.